Pemaknaan Nasionalisme dalam Upaya Pencegahan Illegal Trading di Wilayah Perbatasan - Keraf, Fransiskus Markus Pereto; Mambur, Yohanes Pebrian Vianney; Feka, Yanuarius Sani (Journal of Moral and Civic Education, 2023)
This research was motivated by the low level of nationalism among the people on the border of Indonesia and Timor Leste. There are still people in border areas who practice illegal trading and smuggling of goods. This research aims to prevent illegal trading practices in border areas through the meaning of nationalism. The meaning of nationalism is carried out in the form of carrying out activities that involve all components of society. Sub-district and village officials together with the entire community organize creative activities in interpreting nationalism. A qualitative approach was designed in this research using a case study method. The subjects in this research were youth youth organizations and the general public in Napan Village. Participants in this research were village heads, youth youth organizations, traditional leaders and community leaders. The data collection methods used were observation, interviews and documentation. Data analysis techniques consist of reduction, presentation and drawing conclusions. This research concludes that through torchlight parades and giant flag raising activities, it is possible to develop an attitude of nationalism among people on the border. Violations of illegal trading practices can be prevented through the meaning of nationalism in the form of torchlight parades and giant flag flying. This research also has implications for Napan Village, namely that it must immediately make village regulations. This regulation can constitutionally protect the Village government against the practice of smuggling of goods and illegal trading.